Spatio-temporal Analysis of Forest Fires in Portugal - Dias, I.S. (2012)
In the last decade, forest res have become one of the worst natural disasters in Portugal, causing great forest devastation, leading to both economic and environmental losses and putting at risk populations and the livelihoods of the forest itself. In this paper we present Bayesian hierarchical models to analyze spatio- temporal re data on the proportion of burned area in Portugal, by municipalities and over three decades. Mixture of distributions was employed to model jointly the proportion of area burned and the excess of no burned area for early years. For getting estimates of the model parameters, we used Monte Carlo Markov chain methods.